Pengaruh Gaya Kepemimpinan Transformasional, Budaya Organisasi dan Lingkungan Kerja terhadap Kinerja Karyawan PT. ” X ” Sidoarjo: The Influence of Transformational Leadership Style, Organizational Culture and Work Environment on Employee Performance at PT. “X” Sidoarjo - Andriani, Dewi (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2016)
This study aims to determine the effect of Style of Transformational Leadership, Organizational Culture and Work Environment on Employee Performance either partially or simultaneously. And to determine the most significant effect between the influence of the Style of Transformational Leadership, Organizational Culture and Work Environment on Employee Performance at PT.”X” Sidoarjo. This study used data tabulation of the results of the questionnaire respondents. The sample used in this study were 57 employees at PT.”X” The analytical tool used is multiple linear regression analysis, the coefficient of determination (R2), the partial correlation coefficient, t test, F test and classical assumption by using SPSS version 17 for Windows. Primary data was obtained from a questionnaire that the measurement using a Likert scale that tested the validity and reliability. The results based on test validity and reliability of the data indicates that is valid and reliable. Based on t test and F test showed that the Style of Transformational Leadership, Organizational Culture and the Working Environment and simultaneous partial effect to the Employee Performance. Between the Style of Transformational Leadership, Organizational Culture and the Working Environment which has the most significant effect toward employee’s performance is organizational culture.